2022
DOI: 10.1371/journal.pone.0266463
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position and self-rated health among female and male adolescents: The role of familial determinants in explaining health inequalities. Results of the German KiGGS study

Abstract: Objective Although health inequalities in adolescence are well documented, the underlying mechanisms remain unclear. Few studies have examined the role of the family in explaining the association between the family’s socioeconomic position and adolescents’ self-rated health. The current study aimed to explore whether the association between socioeconomic position and self-rated health was mediated by familial determinants. Methods Using data from wave 2 of the”German Health Interview and Examination Survey f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Results show a social gradient in self-rated health with children with lower SES experience worse health (Kuntz et al, 2018 ). This finding is confirmed by Rattay et al ( 2022 ) who analyze the same dataset focusing on adolescents and their parents ( N = 3,556; adolescents aged 11–17). Not only do they find a relationship of income (only for girls), education and occupational status separately with self-rated health but also of an SES index and health.…”
Section: Theoretical Background and Previous Researchsupporting
confidence: 71%
“…Results show a social gradient in self-rated health with children with lower SES experience worse health (Kuntz et al, 2018 ). This finding is confirmed by Rattay et al ( 2022 ) who analyze the same dataset focusing on adolescents and their parents ( N = 3,556; adolescents aged 11–17). Not only do they find a relationship of income (only for girls), education and occupational status separately with self-rated health but also of an SES index and health.…”
Section: Theoretical Background and Previous Researchsupporting
confidence: 71%
“…Although the expansion of education in the last decades had improved the access to higher education across all social classes, there was still a bias toward children from a higher socio-economic background being more likely to be enrolled at universities. We found that the importance of the socio-economic status of parents for the health of their offspring was still persistent among university students, a connection that was already known for adolescents (41) and young children (42). This showed that the "social class" of origin had more persistence than the aspired social class as suggested by Hagquist (14).…”
Section: Discussionmentioning
confidence: 62%
“…However, we found evidence for the relevance of ECEC center sports focus for BMI for boys only. Therefore, it might be speculated that for boys' factors outside the family might be relevant concerning BMI, whereas for girls, the family SEP seems to play a more important role ( 44 ). Our finding is all the more surprising considering that girls are known to have more sedentary lifestyles and lower levels of physical activity than boys ( 45 ).…”
Section: Discussionmentioning
confidence: 99%